Computer Programming Aptitude Test as a Tool for Reducing Student Attrition - Borzovs, Juris; Niedrite, Laila; Solodovnikova, Darja (My University, 2015)
The stable trend to lose from one-third to half of students in the first study year of computing studies motivated us to explore, which methods are used to determine in advance such applicants, who have no change to overcome the first study year. Initially, a research about the factors influencing the attrition in Faculty of Computing at the University of Latvia was conducted. The research revealed that the trend of non-beginning studies might indicate the wrong choice of the study field and possible lack of understanding of what is programming by enrolled students (applicants as well as pupils). The study provides the review of the situation with programming aptitude tests in the world, which could serve as one of the solutions to the dropout reduction. An action plan is proposed, which is based on the exploration of students and evaluation of activities already conducted at the Faculty of Computing of the University of Latvia to reduce dropout (School of Young Programmers, Compensative Course in High School Mathematics, Mentoring programs). Moreover, the supplementation of these activities by one of the existing programming attitude tests (or a combination of several tests) or a necessity to develop a new similar test is considered.
Submitted to the VTR conference to be held in Rezekne, June 2015
Keywords: computer science education; attrition rate; aptitude test; data analysis